The Influence of Instagram Social Media Against Traveling Interest - Muhammad Miftakhur Rizky; Tutut Nofita Sari (International Consortium of Education and Culture Research Studies, 2020)
This study aims to discuss the influence of Instagram social media on traveling interest using the theory of interest in visiting Philip Kotler, et al., (2006: 198) in Marketing for Hospitality and Tourism assumes that buying interest in consumers can be equated with interest in visiting tourists. This can be seen in the same behavior. There is no related theory regarding interest and decision to visit, but in accordance with Kotler's theory, et al., That visiting interest is included with purchase interest measured by the same indicator. Data is collected by distributing questionnaires to respondents. The data analysis that we use is a simple linear regression. The results showed that the Instagram Traveling Social Media variable had a significant effect on Visiting Interest (Y) followers to a destination). It is known that the beta coefficient of this analysis is 73.1% and 16.9% is influenced by other variables not included in this study. Instagram Social Media Variable Indicator which is dominant influence is the hashtag indicator with a mean value of 4.28 and the item that dominates the hashtag indicator is the Instagram Traveling account that gives messages using a hashtag that can be used to disseminate photos so that followers can easily find them. While the indicator on the Traveling Interest Variable that has a dominant influence is transactional interest with a mean value of 3.97 that respondents are interested in visiting a place to take photos and are interested in the uniqueness of the tourist attractions.